Post a New Question

algebra

posted by on .

simplify the expression
-6+i/-5+i
Could someone explain the steps?

  • algebra - ,

    recall that (a+bi)(a-bi) = a^2+b^2

    to get that pesky complex number out of the denominator, multiply by (-5-i) top and bottom:

    (-6+i)(-5-i)/(-5-i)(-5+i)
    = (30 - 5i + 6i - i^2)/26
    = (31 + i)/26
    = 31/26 + 1/26 i

  • algebra - ,

    thank you

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question